SYSTEMATIC LITERATURE REVIEW : EFEKTIVITAS PEMBELAJARAN BERBASIS GAMIFIKASI DI ABAD 21 UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PADA MATERI BIOLOGI SMA/MA - Ilfana, Azalia Azwa; ‘Arifaturrohmatun, Ulfah; Heriani, Siti Aisah; Noviar, Dian; Utami, Runtut Prih (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
The purpose of this research is to analyze the efficacy of gamification-based learning (Based Learning/GBL) in improving student engagement and academic achievements in high school biology courses within the 21st-century context through a Systematic Literature Review (SLR) methodology. Following the PRISMA guidelines, literature exploration was performed utilizing the Publish or Perish platform with targeted keywords, yielding 18 selected publications that satisfied the inclusion standards. The evaluation demonstrated that GBL creates positive impacts on student motivation, active involvement, and academic performance across various biology topics including ecosystems, biological scope, plantae, and others. Multiple gamification tools, such as Kahoot, Quizizz, Wordwall, and additional educational gaming platforms, have demonstrated effectiveness in establishing captivating, interactive educational settings that facilitate enhanced conceptual comprehension. The results indicate that GBL not only strengthens cognitive abilities but also develops students' affective and psychomotor dimensions. Consequently, GBL demonstrates considerable promise as an innovative approach for biology education that corresponds to 21st-century skill requirementsstudy aims to examine the effectiveness of gamification-based learning